Fuzzy Economic Order Quantity for Items with Imperfect Quality and Inspection Errors in an Uncertain Environment on Fuzzy Parameters - Nithya, K.; Ritha, W. (Journal of Informatics and Mathematical Sciences, 2012)
This article investigates the inventory problem for item received with imperfect quality and inspection errors in an uncertain environment. Two inventory models are discussed with fuzzy parameters for crisp order quantity, or for fuzzy order quantity. Function principle is proposed as an arithmetic operation of fuzzy trapezoidal number to obtain fuzzy economic order quantity and fuzzy annual profit. Graded mean integration method is used for defuzzification of the annual profit. Extension of Lagrangian method is used to find optimal order quantity. Numerical examples are provided to illustrate the results of proposed models.